The Essence and Features of Functioning of Household Lands of Uzbekistan - Ashurov Abdullo Fayzulloevich (International Journal on Integrated Education, 2022)
The socio-economic role of household land plots and personal subsidiary farms is studied, the definitions of their terms are given, and the role of the household land plot in ensuring food security of the country and increasing the export potential of fruits and vegetables is considered. The reasons of higher efficiency of cultivation of agricultural production in personal subsidiary farms in comparison with other forms of managing in agriculture, and also features of use of household land plots are studied.